The role of perceptions of inter-group conflict on religious radicalism: Losing meaning as a mediator - Hermawan, Ardy; Mashuri, Ali (Jurnal Psikologi Tabularasa, 2023)
Indonesia as a country is still facing various kinds of national problems that have not been fully resolved. One of these problems is religious radicalism among some Muslims in this country. Examining the factors that trigger religious radicalism is thus an urgent and relevant scientific effort in Indonesia. To achieve this vision, this study aims to examine loss of significance as a mediator of the role of perceived intergroup conflict that pits Muslims against the West in explaining religious radicalism among some Muslims. This idea was tested using a correlational quantitative method with 201 Muslim participants. The results showed that, first, the higher the perceptions of conflict between Muslims and the West, the higher religious radicalism. Second, the perceived intergroup conflict increased loss of significance, and ultimately, loss of significance significantly explained the high levels of religious radicalism. Third, loss of significance mediated the positive relationship between perceived inter-group conflict and religious radicalism. The results of this study imply that religious radicalism is rooted in situational factors that strengthen individual motivation to support such an extreme, violent action.Indonesia sebagai sebuah negara masih menghadapi berbagai macam masalah nasional yang belum sepenuhnya tertangani. Salah satu permasalahan tersebut adalah radikalisme agama di kalangan sebagian Muslim di negeri ini. Meneliti faktor-faktor yang memantik radikalisme agama dengan demikian merupakan sebuah upaya ilmiah yang urgen dan relevan di Indonesia. Untuk mencapai visi tersebut, penelitian ini bertujuan menguji kehilangan makna (loss of significance) sebagai mediator peran persepsi konflik antar kelompok dalam menjelaskan radikalisme agama di kalangan sebagian Muslim. Ide ini diuji menggunakan metode kuantitatif korelasional Â dengan partisipan Muslim berjumlah 201. Hasil penelitian menunjukkan bahwa, pertama, semakin tinggi persepsi konflik antara Muslim dan pihak Barat maka semakin tinggi radikalisme agama. Kedua, persepsi konflik antar kelompok tersebut meningkatkan kehilangan makna, dan kehilangan makna selanjutnya secara signifikan menjelaskan tingginya radikalisme agama. Ketiga, kehilangan makna berperan signifikan sebagai mediator hubungan positif antara persepsi konflik antar kelompok dan radikalisme agama. Hasil penelitian ini mengimplikasikan bahwa radikalisme agama bermuara pada faktor situasional yang memperkuat motivasi individu untuk mendukung tindakan ekstrim tersebut.